Who gains and who loses from the 2011 debit card interchange fee reform? - Oz Shy (Federal Reserve Bank of Boston, 2012)
In October 2011, new rules governing debit card interchange fees became effective in the United States. These rules limit the maximum permissible interchange fee that an issuer can charge merchants for a debit card transaction. This paper provides simple calculations that identify the transaction values for which merchants pay higher and lower interchange fees under the new rules. The paper then uses new data from the Boston Fed's 2010 and 2011 Diary of Consumer Payment Choice to identify the types of merchants who are likely to pay higher and lower interchange fees under the new rules.
Keywords: G28; 330; Debit card interchange fee